(untitled) - Silberberg, Martin S. (Boston, 2000)
This is a general chemistry text for the two-semester course. Silberberg offers a logical and unique approach to problem-solving, ground-breaking visualization of atomic/molecular interactions, and essential connections between chemical principles and real-world processes.
Keywords: Chemistry,Hóa học